2001
DOI: 10.1029/2000jd000109
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of enhanced H2SO4 and 3–4 nm particles near a frontal cloud during the First Aerosol Characterization Experiment (ACE 1)

Abstract: Abstract. Observations of new particle production recorded near a frontal cloud at-6 km above sea level in a remote marine region are reported. Two distinct locations situated near the cloud were found to have enhanced concentrations of sulfuric acid vapor (H2SO4) and freshly formed 3-4 nm particles. Both were in droplet-free air situated above cloudy regions.No evidence for enhanced H2SO4 or nucleation was observed in clear air far from the cloud.In the nucleating region the aerosol size distribution from 3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 33 publications
5
121
0
Order By: Relevance
“…This limits our ability to quantitatively assess the impacts of particles on visibility, human health and climate change as well as to develop effective control strategies. 1,12 Field measurements have shown that sulfuric acid (H 2 SO 4 ) is a key species for NPF, [13][14][15] possibly with the involvement of organic compounds. [16][17][18] The presence of ammonia (NH 3 ) can stabilize nucleating clusters, and enhance nucleation by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…This limits our ability to quantitatively assess the impacts of particles on visibility, human health and climate change as well as to develop effective control strategies. 1,12 Field measurements have shown that sulfuric acid (H 2 SO 4 ) is a key species for NPF, [13][14][15] possibly with the involvement of organic compounds. [16][17][18] The presence of ammonia (NH 3 ) can stabilize nucleating clusters, and enhance nucleation by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…cm −3 s −1 , and κ=[0.5, 1, 1.5, 2, 1000] days. The production values of sulphuric acid were chosen such that the sulphuric acid gas concentration reached peak values of about 1×10 7 cm −3 comparable to the values of and Weber et al (2001). Note that this may be at the high end of the sulphuric acid concentration range.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…However the exact mechanism controlling the early stages of aerosol formation is still not understood. Several measurements of atmospheric nucleation have been reported where the observed nucleation rates cannot be explained by the traditional theory of binary homogeneous nucleation by water and sulphuric acid (Hoppel et al, 1994;Weber et al, 1996;Weber et al, 1997;Clarke et al, 1998;O'Dowd et al, 1999;Weber et al, 2001a;Birmili et al, 2003). A ternary nucleating agent such as ammonia has been proposed to enhance the nucleation process by stabilising early cluster formation (Weber et al, 1996;O'Dowd et al, 1999;Weber et al, 1998;Kulmala et al, 2000).…”
Section: Introductionmentioning
confidence: 99%